Analysis of the agreement on fall records between electronic health records and notifications: cohort study (Research, Society and Development, 2020)
Objective: To analyze the agreement on fall records between patient progress data in electronic health records and notifications by the Incident Reporting System. Method: Retrospective cohort study conducted at a public hospital in Porto Alegre, Rio Grande do Sul, Brazil. The sample consisted of 367 patients, 441 self-reported notifications and 441 patient progress notes. Data were collected from the online annotation system WebAnno between September and December 2018. A collection instrument was developed. Data analysis was performed through descriptive statistics. Data were analyzed using the Statistical Package for the Social Sciences, SPSS Inc., Chicago, version 17.0 for Windows. Results: Among the patients, 316 had one fall and 51 had two falls or more. The study included 441 fall notifications. Of these, 43.9% were not recorded in the electronic medical records on the day of their occurrence. Regarding the record of risk assessment for falls, only three (0.7%) progress notes contained it.  More complete records were identified in the notifications as compared to the electronic health records. The results related to fall location, recorded in all notifications and in 13.8% of the progress notes, and damage degree, recorded in all notifications and in only 1.6% of the progress notes, are noteworthy. Conclusion: A gap of records for falls in electronic health records was identified. The results point to an aspect of extreme relevance in terms of communication via patients’ electronic health records, which can directly influence the planning and implementation of effective care.